Hot Hydride Superconductivity Above 550 K - Grockowiak, A. D.; Ahart, M.; Helm, T.; Coniglio, W. A.; Kumar, R.; Glazyrin, K.; Garbarino, G.; Meng, Y.; Oliff, M.; Williams, V.; Ashcroft, N. W.; Hemley, R. J.; et al. (Frontiers in Electronic Materials, 2022)
The search for room temperature superconductivity has accelerated in the last few years driven by experimentally accessible theoretical predictions that indicated alloying dense hydrogen with other elements could produce conventional superconductivity at high temperatures and pressures. These predictions helped inform the synthesis of simple binary hydrides that culminated in the discovery of the superhydride LaH10 with a superconducting transition temperature Tc of 260 K at 180 GPa. We have now successfully synthesized a metallic La-based superhydride with an initial Tc of 294 K. When subjected to subsequent thermal excursions that promoted a chemical reaction to a higher order system, the Tc onset was driven irreversibly to 556 K. X-ray characterization confirmed the formation of a distorted LaH10 based backbone that suggests the formation of ternary or quaternary compounds with substitution at the La and/or H sites. The results provide evidence for hot superconductivity, aligning with recent predictions for higher order hydrides under pressure.